Effect of a rehabilitation skill program using resistance bands on biokinetic variables in volleyball players with disabilities - Ibrahim, Reem Salam (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
To achieve high level of performance in sports games and events, all aspects, including the motor, tactical, psychological and skill performance of the players must be integrated and improved. Rubber bands play an important role in player rehabilitation to speed up muscle recovery in a good way. The aim of the study was to prepare a rehabilitation skill program using rubber bands to develop the preparation skills and biokinetic variables for volleyball players with disabilities in wheelchairs. The experimental method was used in one of its basic designs which is the design of the two equivalent groups, this due to the suitability of this design to the nature of the research problem. The research sample was chosen by a comprehensive inventory method and consisted of 18 disabled volleyball players of Babylon governorate for the 2021 season. The sample was divided into two groups, the experimental group and the control group, with 9 players for each group. A rehabilitative skill program was prepared using rubber bands on the experimental group for a period of eight weeks, with three training units per week. Data were analyzed based on arithmetic means, standard deviations and t-test. As a result, statistically significant differences were found between the pre-test and post-test of the experimental group and the control group for all study variables, in favor of the post-test for both groups (p<0.05). In conclusion, the rehabiliation skill program using rubber bands has a positive effect on the development of the preparation skills and biokinetic variables for volleyball players with disabilities in wheelchairs.